Pengaruh Pemberian Baby Massage Menggunakan Virgin Coconut Oil Terhadap Kualitas Tidur pada Bayi usia 3 – 10 Bulan - Atik Aryani; Widiyono Widiyono; Shinta Rositasari; Anik Suwarni (Jurnal Ilmu Keperawatan Anak, 2022)
Sleep is a main priority for babies, because at this time neuro-brain repair occurs and approximately 75% of growth hormone is produced. Sleep has a major impact on mental, emotional, and physical health, as well as the immune system. Babies who are sleep deprived are more susceptible to signs of impaired intelligence, such as difficulty concentrating, poor memory and loss of creativity. One of the factors that can affect growth and development is sleep quality. The quality of baby sleep can be stimulated through the act of giving baby massage. The purpose of this study was to analyze the effect of giving baby massage using Virgin Coconut Oil on sleep quality in infants aged 3-10 months. The design of this study used one group pre-test post-test group. The sampling technique was done by purposive sampling with the number of respondents as many as 16 infants aged 3 -10 months at the Toddler Posyandu, Pabelan Village, Kartasura, Sukoharjo. Data collection using the Brief Infant Sleep Questionnaire instrument to measure sleep quality. Data analysis in this study used the Wilcoxon Signed Rank Test. The results showed that before being given massage the majority of the baby's sleep quality was poor, as many as 11 respondents (68.8%), then after being given a massage for 3 weeks there was an increase in sleep quality where as many as 14 respondents (87.5%) had good sleep quality. The results of the comparison test of baby massage between before and after massage with VCO obtained a p value of 0.002 (p value <0.05). Conclusion: there is an effect of baby massage using VCO on the quality of sleep in infants aged 3 -10 months.